Comparative genome analysis investigation of nosocomial and community-acquired cases of Legionnaires’ disease caused by ST2858 and ST378 - Maria Najeeb; Gillian Cameron; Marianne Grimard-Conea; Sara Matthews; Julie Brodeur; Geneviève Cadieux; Pierre A. Pilon; Xavier Marchand-Senécal; Cindy Lalancette; Martin Smith; Michèle Prévost; Sebastien P. Faucher (Microbiology Spectrum)
ABSTRACT Eight cases of Legionnaires’ disease caused by Legionella pneumophila serogroup 1 sequence type (ST) ST2858 were detected within 4 years in Montréal, Canada. Most cases were associated with a single healthcare facility, and one of them presented with a co-infection, from which ST378 was isolated as well. The source of ST2858 was not identified, despite extensive environmental sampling. The goal of this study was to determine the diversity of both STs and confirm the source of each by matching clinical to environmental isolates. Comparative genome analysis was performed to investigate the genetic relatedness of the isolates. Long- and short-read hybrid assembly was used to produce high-quality closed genomes. A PCR assay, amplifying a unique gene of ST2858, was also developed. None of the 599 environmental isolates screened by PCR was ST2858. The ST2858 clinical isolates had a maximum of two single nucleotide polymorphisms in pairwise comparison, suggesting a common source. ST378 isolates had higher genomic diversity, and the isolate from the co-infection was similar to environmental ST378 from the healthcare facility’s hot water distribution system. The isolate from the co-infection harbored a plasmid conferring increased copper resistance. Understanding genomic diversity could help identify potential sources and should be considered for matching clinical with environmental isolates. Phenotypic diversity may be relevant for outbreak investigation, surveillance, and management.IMPORTANCELegionnaires’ disease (LD) is transmitted to humans by inhalation of aerosols contaminated with Legionella. When an outbreak occurs, identification of the source allows public officials to make sure the source is controlled to prevent further cases. In this study, whole genome sequencing was used to investigate the relatedness between clinical and environmental isolates collected during the epidemiological investigation of cases of LD centered around a single healthcare facility, providing valuable information about the diversity of Legionella within water systems and similarity thresholds for matching clinical and environmental strains. The genomic data were also used to design a methodology to rapidly screen hundreds of historical isolates and DNA extracts, which could benefit source identification in other outbreaks. Furthermore, Legionella isolates may differ in their ability to resist disinfection methods and potentially acquire novel genetic determinants, and water system characteristics may select for specific Legionella strains.